Answer:
Arithmetic sequence.
Common difference = -x - 11
Explanation:
This is an arithmetic sequence.
-3x - 7, -2x - 9, -x - 11, ...
Find the common difference.
Common difference =second term - first term.
= -2x - 9 - (-3x - 7)
= -2x - 9 + 3x +7
= -2x + 3x - 9 + 7 {Combine like terms}
= x - 2
If we add the common difference to the second term, we will get the third term.
Third term = second term + common difference
= -2x - 9 + x - 2
= -2x + x - 9 - 2
= -x - 11.
Hence this is an arithmetic sequence.